Is traditional Chinese medicine recommended in Western medicine clinical practice guidelines in China? A systematic analysis. Issue 6 (3rd June 2015) - Ren, Jun; Li, Xun; Sun, Jin; Han, Mei; Yang, Guo-Yan; Li, Wen-Yuan; Robinson, Nicola; Lewith, George; Liu, Jian-Ping
Abstract : Background: Evidence-based medicine promotes and relies on the use of evidence in developing clinical practice guidelines (CPGs). The Chinese healthcare system includes both traditional Chinese medicine (TCM) and Western medicine, which are expected to be equally reflected in Chinese CPGs. Objective: To evaluate the inclusion of TCM-related information in Western medicine CPGs developed in China and the adoption of high level evidence. Methods: All CPGs were identified from the China Guideline Clearinghouse (CGC), which is the main Chinese organisation maintaining the guidelines issued by the Ministry of Health of China, the Chinese Medical Association and the Chinese Medical Doctors' Association. TCM-related contents were extracted from all the CPGs identified. Extracted information comprised the institution issuing the guideline, date of issue, disease, recommendations relating to TCM, evidence level of the recommended content and references supporting the recommendations. Results: A total of 604 CPGs were identified, only a small number of which (74/604; 12%) recommended TCM therapy and only five guidelines (7%) had applied evidence grading. The 74 CPGs involved 13 disease systems according to the International Classification of Diseases 10th edition. TCM was mainly recommended in the treatment part of the guidelines (73/74, 99%), and more than half of the recommendations (43/74, 58%) were related to Chinese herbal medicine (single herbs or herbal treatment based on syndrome differentiation). Conclusions: Few Chinese Western medicine CPGs recommend TCM therapies and very few provide evidence grading for the TCM recommendation. We suggest that future guideline development should be based on systematic searches for evidence to support CPG recommendations and involve a multidisciplinary approach including TCM expertise.